2017
DOI: 10.4236/ajps.2017.85077
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and Antioxidative Effects of <i>Glossogyne tenuifolia</i> on Streptozotocin-Nicotinamide-Induced Diabetic Rats

Abstract: Glossogyne tenuifolia (GT) is the traditional herbal tea in Penghu Island, Taiwan. Recent research has shown that the active components in GT are potential inhibitors of α-glucosidase. The present study investigated that whether or not GT could improve the status of type 2 diabetes mellitus. Male Wistar rats aged eight weeks were induced to be hyperglycemic by subcutaneous injection of streptozotocin-nicotinamide (STZ-NA) and combination of high-fat diet (HFD). The animals were given GT extracts at the low dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Extracts of GT are traditionally been used to prepare herbal drink that provide protection against sunstroke but there is a long history of it being used as a remedy in the local Folk medicine for their antipyretic, hepatoprotective and anti-inflammatory effects [15, 16, 19–23]. Administration of GT extract in Streptozotocin (STZ)–nicotinamide (NA)-induced diabetic rats have shown to inhibit α-glucosidase in vitro and enhance anti-oxidative capacity and hypoglycemic effect [15, 24]. Several bioactive principles in GT extracts have been identified and shown to provide both anti-inflammatory and anti-viral effects with respect to production of signaling mediators, like TNF-alpha, IL-6 and IFN-gamma, in human blood [25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of GT are traditionally been used to prepare herbal drink that provide protection against sunstroke but there is a long history of it being used as a remedy in the local Folk medicine for their antipyretic, hepatoprotective and anti-inflammatory effects [15, 16, 19–23]. Administration of GT extract in Streptozotocin (STZ)–nicotinamide (NA)-induced diabetic rats have shown to inhibit α-glucosidase in vitro and enhance anti-oxidative capacity and hypoglycemic effect [15, 24]. Several bioactive principles in GT extracts have been identified and shown to provide both anti-inflammatory and anti-viral effects with respect to production of signaling mediators, like TNF-alpha, IL-6 and IFN-gamma, in human blood [25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the combination of high fat diet (HFD) with STZ has been reported to induce IR and hyperglycemia [18]. Nicotinamide has been shown to mediate a partial protection against cellular damage induced by STZ [19]; thus, this animal model mimics human T2DM with IR [10,20].…”
Section: Discussionmentioning
confidence: 99%
“…A second dose of NA and STZ were administered 24 h later. After induction, the animals in this group were switched to a high fat diet (40% energy from fat) [10]. A week later, rats with a fasting blood glucose (FBG) between 180 and 220 mg/dL were considered diabetic and included in the study [11].…”
Section: Induction Of Diabetesmentioning
confidence: 99%
“…In our previous studies, we showed that GT extract has antioxidant and hepatoprotective activities against acetaminophen-induced hepatotoxicity and high-fat-diet-induced diabetes [ 14 , 18 ]. Furthermore, we have also shown the hypoglycemic and hypolipidemic effects of GT extracts in animal models [ 13 , 19 ]. We have also shown the presence of major phenolic compounds, such as luteolin, luteolin-7-glucoside, and oleanolic acid, in GT extract by HPLC analysis Figure 1 [ 14 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%